2014
DOI: 10.1002/fsn3.119
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial‐resistant genes associated with Salmonella spp. isolated from human, poultry, and seafood sources

Abstract: Antimicrobial-resistant salmonellosis is a significant public health concern globally. A study was conducted to screen for Salmonella species from a total of 120 samples, of which 50 were retail meat samples purchased from five randomly selected sales outlets in the city of Mangalore, India. Twenty poultry fecal materials freshly voided before slaughter were obtained with sterile spatula and placed in sterile sealable polythene envelopes, and 20 clams were purchased from the estuaries of Nethravathi and Kankar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
52
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 28 publications
13
52
1
Order By: Relevance
“…The S. Typhimurium exhibited high rates of resistance to traditional antibiotics such as ampicillin, nalidixic acid, tetracycline and sulfamethoxazole-trimethoprim; this is in accordance with the findings of other authors [35,36]. The detection of antimicrobial genes and a strict policy for the rational use of antibiotics for treating animals and humans is needed, if we do not want to have to limit the therapeutical choices for treating salmonellosis [5].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The S. Typhimurium exhibited high rates of resistance to traditional antibiotics such as ampicillin, nalidixic acid, tetracycline and sulfamethoxazole-trimethoprim; this is in accordance with the findings of other authors [35,36]. The detection of antimicrobial genes and a strict policy for the rational use of antibiotics for treating animals and humans is needed, if we do not want to have to limit the therapeutical choices for treating salmonellosis [5].…”
Section: Discussionsupporting
confidence: 81%
“…Multidrug-resistant (MDR) Salmonella strains have been among the major public health concerns worldwide [4]. Subsequent transmission of antimicrobial resistance to humans can be in the form of either resistant pathogens or commensal organisms carrying transferable resistance genes [5].…”
Section: Introductionmentioning
confidence: 99%
“…Chloramphenicol was used to treat MDR infections in human and animals [55][56][57]. The sulfisoxazole resistance genes sul1 (located within 3'-conserved segment [3'-CS] of class 1 integrons) and sul2 (associated with small multicopy plasmids or large transmissible multiresistance plasmids) are the most frequently found genes for sulfonamide resistance among sulfonamide-resistant isolates from food animals and humans, whereas sul3 is detected in various large Salmonella plasmids [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Escherichia coli O104:H4 was found to be resistant to at least 14 different antibiotics (Verstraete et al 2013), and about 90% of Salmonella isolates were found to be resistant to one or more antibiotics tested (Dias de Oliveira et al 2005;Wang et al 2014;Liang et al 2015). Some Salmonella isolates from poultry were found to be resistant to 14 different antibiotics (Adesiji et al 2014;Zhang et al 2014). Moreover, 95% of nosocomial infections are caused by resistant staphylococci (National Center for Health Statistics 2009).…”
Section: The Rise Of Antibiotic Resistance and Phage Revitalizationmentioning
confidence: 99%